Cisplatin efflux, binding and intracellular pH in the HTB56 human lung adenocarcinoma cell line and the E-8/0.7 cisplatin-resistant variant. - Chau, Quincy Ka-Hing. (University of Ottawa (Canada), 1999)
The total cellular ([T-DDP]), intracellular ultrafilterable ([F-DDP]) and precipitable cellular bound ([B-DDP]) cisplatin concentrations were all compared in the HTB56 human lung adenocarcinoma call line and its E43/0.7 variant that has acquired cisplatin resistance. After a 20-minute exposure to 509muM cisplatin, uptake was terminated by spinning cell suspensions in a microcentrifuge at 14000 rpm for 10s. Ultrafiltration with a 500 molecular weight cut-off separated cellular free from bound cisplatin. Fragmentation by sonication and micro-centrifugal spinning precipitated cellular bound cisplatin. Flow cytometry was used to measure the intracellular pH (pHi) of the HTB56 cell line, the E8/0.7 cell lines, the OV2008 cell line and its C13 resistant variant, as well as of the A2780 and its A2780/CP resistant variant. The DNA-bound DDP and Protein-bound DDP ([P-DDP]) were also compared when equal [T-DDP] was achieved for both sensitive and resistant lung cancer cells by exposing them to two pairs of DDP concentrations, i.e., 509 vs 911 muM DDP, and 111 vs 666 muM DDP respectively. After one-hour drug exposure in these equal loading experiments, uptake was terminated and cells were scraped. Platinum was assayed by flameless atomic absorption spectrophotometry. (Abstract shortened by UMI.)
Keywords: Biology, Cell.